Students’ perceptions towards multimedia elements in Sounds and Pronounce Interactive Software (SPISE) for English / Sueb Ibrahim, John Francis Noyan, Lilly Metomand, Ismariani Ismail and Lenny Yusrina Bujang Khedif - Ibrahim, Sueb; Noyan, John Francis; Metomand, Lilly; Ismail, Ismariani; Bujang Khedif, Lenny Yusrina (Universiti Teknologi MARA, Kedah, 2019)
This paper presents students’ perceptions towards multimedia elements in Sounds and Pronounce Interactive Software (SPISE) for English. SPISE is an interactive multimedia software, which attempts to introduce learners to the English phonetic system. It is a learning aid that teaches learners the correct pronunciation of English words. The collection of data for this research paper involved the administration of questionnaires to 74 students of SK TASUDA (Tan Sri Sulaiman Daud), Kuching, Sarawak, comprising Primary 5 and 6 students. Prior to the distribution of questionnaires, the participants were guided on how to use SPISE, and they experienced learning the English phonetics using the software. From the findings, high responses were obtained for the software’s interface, text, graphic, audio, interactivity and effectiveness (above 3.80). In addition, as SPISE promotes self-directed learning by providing immediate feedback, the students found the learning fun and interactive. Hence, it could be concluded that SPISE is a useful, fun and interactive software for a teaching and learning aid, which could help learners master their English phonetics.